Literacy of children from school to life: the SAESE and SAEB assessment on the initiation of reading and writing in the state of Sergipe - Nunes, Suzana Mary de Andrade (Debates em Educação, 2024)
This study aims to analyze and establish connections between SAESE, SAEB and the School Census, in order to carry out a qualitative study of their indicators between 2021 and 2024. To this end, we reflect on the historical issues that underpin discrimination and prejudice, understanding that the impacts resulting from culture are represented in the results of local and national assessments of the different states of the federation. In this sense, we start from the understanding that the schooling of children in the early years must take into account social, historical and political contexts, so that the educational policies of a common curriculum do not reinforce inequalities, but rather strengthen the democratic principle of regional and national equity.